Primary Immunodeficiency Disorders (PIDs) and its Rheumatologic Manifestations Mohammad Imnul Islam - Islam , Mohammad Imnul (Bangladesh Journal of Child Health, 2024)
The hallmark of Primary Immunodeficiency Disorders (PIDs) is increased susceptibility to recurrent infections, which are often poorly responsive to therapy, prolonged and life-threatening. The infections can involve bones and joints. PIDs may also predispose to allergic, autoimmune, autoinflammatory and malignant disorders. Arthritis is the most common rheumatological manifestation of PIDs. Recurrent septic arthritis, arthritis with increased susceptibility to infection, skeletal changes, autoimmune disease or systemic lupus erythematosus with negative antinuclear antibody (ANA) are the essential clinical clues that could be considered rheumatologic manifestations of PIDs. This is considerable concern that early detection of PIDs patients invariably improves the quality of life and life expectancy through the prompt implementation of appropriate medical intervention. BANGLADESH J CHILD HEALTH 2022; VOL 46 (2) : 82-85